Hydrostatic pressure, impurity position and electric and magnetic field effects on the binding energy and photo-ionization cross section of a hydrogenic donor impurity in an InAs Pöschl-Teller quantum ring - Barseghyan, M. G.; Mora-Ramos, M. E.; Duque, C. A. (The European physical journal. B, Condensed matter physics, 2011)
Using the variational method and the effective mass and parabolic band approximations, the behaviour of the binding energy and photo-ionization cross section of a hydrogenic-like donor impurity in an InAs quantum ring, with Pöschl-Teller confinement potential along the axial direction, has been studied. In the investigation, the combined effects of hydrostatic pressure and electric and magnetic fields applied in the direction of growth have been taken into account. Parallel polarization of the incident radiation and several values of the applied electric and magnetic fields, hydrostatic pressure, and parameters of the Pöschl-Teller confinement potential were considered. The results obtained can be summarised as follows: (1) the influence of the applied electric and magnetic fields and the asymmetry degree of the Pöschl-Teller confinement potential on the donor binding energy is strongly dependent on the impurity position along the growth and radial directions of the quantum ring, (2) the binding energy is an increasing function of hydrostatic pressure and (3) the decrease (increase) in the binding energy with the electric and magnetic fields and parameters of the confinement potential (hydrostatic pressure) leads to a red shift (blue shift) of the maximum of the photo-ionization cross section spectrum of the on-centre impurity.